Efektivitas Penggunaan Dana Desa dalam Pelaksanaan Pembangunan Di Kecamatan Tapaktuan Kabupaten Aceh Selatan - Yuliana Yuliana; Isthafan Najmi; Yulfrita Adamy; Hendra Sasmita (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to determine the use of village funds in the implementation of development in the Tapaktuan District, South Aceh Regency and to determine the effectiveness of the use of village funds in the implementation of development in the Tapaktuan District, South Aceh Regency. This research uses a quantitative descriptive approach. The type of data used is in the form of secondary data, namely Target and Realization Data in the Tapaktuan District, 2017 to 2019 along with Target Data and the realization of Village Fund Receipts in the Tapaktuan District, 2017 to 2019. Data collection using documentation techniques. Data analysis used qualitative and quantitative analysis (mix method). Based on the results of the study, it is known that the use of village funds in the implementation of development in the Tapaktuan District, South Aceh Regency as a whole is classified as an average effective. The absorption of the existing budget has not fulfilled one hundred percent, but on average ranges from 30 to 99 percent. Based on the data in table 1.4 Recapitulation of Target and Realization of Village / Gampong Funds for Each Village in the Tapaktuan sub-district, South Aceh Regency for the 2017-2019 Fiscal Year, we can conclude that from a total of 16 villages in the Tapaktuan sub-district, the village with the highest percentage of budget absorption is Panjupian Village. with a percentage of 99.91% in 2017 with the effectiveness criteria being Very Effective, while the Village with the lowest percentage of budget absorption was Air Pinang Village with a percentage of 30.42% in 2019 with the effectiveness criteria being Ineffective. Meanwhile, the effectiveness of the use of village funds in the implementation of development in Tapaktuan District, South Aceh District, if you look at the realization of the use of village funds for each village, it is considered effective.